Anomalous Origin of the Left Main Artery from Right Coronary Sinus with a Prepulmonic Course. Issue 2 (30th December 2015) - Kaplanoglu, Hatice; Beton, Osman; Dinc, Lale; Kaya, Hakki; Yilmaz, Burhan
A 32 year old female patient presented to the cardiology clinic with an atypical chest pain. Her history revealed no other condition than Leopard syndrome which was diagnosed on her birth. On her coronary CT angiography, LMCA originated from the right coronary sinus and had a prepulmonic course. The purpose of this article is to present this patient with Leopard syndrome accompanied by left coronary artery outlet and coronary sinus abnormality.